The Poetics of Food Consumption: Alimentary Rhetorics and Creative Practices - Barberani, Silvia (Richtmann Publishing, 2012)
Contemporary society is characterized by the spread of contradictory discourses around food, by alimentary hyper-reflexivityand by the gradual individualization of food choices and alimentary-related risks. Food has increasingly become a means of personal(e.g. nutritionism, scientific and spontaneous dietaries, eating disorders, consumption of industrial organic products) and global(alternative modalities of production and consumption) identity management, and a tool that allows for the construction of newsubjectivities, forms of belonging and planning, and of specific worldviews. My hypothesis is that individuals select, manipulate andutilize hegemonic food rhetorics to create new forms of self-representation and belonging, to subscribe to and to question values, and toexplore alternative meaning-making possibilities. This paper is intended as a critical examination of some of the contemporaryhegemonic discursive fields (nutritionist rhetoricals, advertising narratives, techniques of food traceability and labeling, certification,speeches which promote alternative food production and consumption) that determine individual and collective food choices andconsumption practices. In this sense, food may be considered as a